Dodoviscin A Inhibits Melanogenesis in Mouse B16-F10 Melanoma Cells - Yan, Guirui; Zhu, Jingjie; Zhang, Laibin; Xu, Zhijian; Wang, Gaihong; Zhu, Weiliang; Hou, Aijun; Wang, Heyao (Planta Medica, 2013)
Nowadays, abnormal hyperpigmentation in human skin such as melasma, freckles, and chloasma has become a serious esthetic problem. Cutaneous depigmenting agents could be used to treat these hyperpigmentation-associated dieseases. Dodoviscin A is a natural product isolated from the aerial parts of Dodonaea viscosa. In the present study, we evaluated the effect of dodoviscin A on melanin production in B16-F10 melanoma cells for the first time. We found that dodoviscin A inhibited melanin biosynthesis induced by 3-isobutyl-1-methylxanthine and PD98059 significantly, and there was no obvious effect on the viability of dodoviscin A-treated B16-F10 cells. Meanwhile, dodoviscin A could suppress the activity of mushroom tyrosinase in the cell-free assay system and also decrease 3-isobutyl-1-methylxanthine-induced tyrosinase activity and expression of mature tyrosinase protein in B16-F10 cells. Western blotting analysis showed that dodoviscin A inhibited 3-isobutyl-1-methylxanthine and forskolin-induced phosphorylation of the cAMP response element binding protein in B16-F10 cells. These results indicate that dodoviscin A may be a new promising pigmentation-altering agent for cosmetic and therapeutic applications.
Keywords: dodoviscin A; Dodonaea viscosa; Sapindaceae; melanogenesis; tyrosinase; CREB